Floristic composition of dairy cattle pastures in the Peruvian Northern Highlands - Carrasco Chilón, William Leoncio; Alvarez García, Wuesley Yusmein; Vallejos Fernández, Luis Asunción; Vásquez Pérez, Héctor Vladimir (E-Cronicon, 2021)
To optimize cattle consumption and nutrition, it is essential to know the botanical characteristics of the pastures they consume. Therefore, the objective of the present research work was to evaluate the floristic composition, the productive performance of pastures and the productivity of dairy cattle on cattle farms in the inter-Andean valley of Cajamarca. The research was carried out in 10 dairy farms, under a mixed production system, with a stocking rate between 1.8 and 5.3 animal units per hectare. The floristic composition of the forage floor was determined using the “step transect” method to determine the desirable and undesirable species for livestock, considering the age of the pasture from 35 to 45 days and before grazing. A total of seven dominant species were found, of which Lolium multiflorum L. - “Cajamarquino ecotype”, Trifolium pratense and Trifolium repens are desirable species for livestock and represent on average 44.84% of the forage floor, the difference being represented by weeds or undesirable species such as: Pennisetum clandestinum, Rumex obtusifolius, Taraxacum officinale and Plantago major. Also, the average biomass yield was 3.33 t. ha-1 with protein levels of 9.96%. The forage yield is low, which affects the animal carrying capacity and consequently the production of the dairy cows, ranging from 5.83 to 16.22 kg milk/day on average, showing very variable and with low profitability.